R&D and Technology Transfer: Firm-Level Evidence from Chinese Industry - Hu, Albert G. Z.; Jefferson, Gary H.; Jinchang, Qian (The Review of Economics and Statistics, 2005)
In bridging the technology gap with the OECD nations, developing economies have access to three avenues of technological advance: domestic R&D, technology transfer, and foreign direct investment. This paper examines the contributions of each of these avenues, as well as their interactions, to productivity within Chinese industry. Based on a large data set for China's large and medium-size enterprises, the estimation results show that in-house R&D significantly complements technology transfer—whether of domestic or foreign origin. Foreign direct investment, which we assume is an important channel of proprietary technology transfer, does not facilitate the transfer of market-mediated foreign technology.